2013
DOI: 10.1590/s0100-879x2013005002515
|View full text |Cite
|
Sign up to set email alerts
|

TNNI3K is a novel mediator of myofilament function and phosphorylates cardiac troponin I

Abstract: Quercetin (Que), a plant-derived flavonoid, has multiple benefical actions on the cardiovascular system. The current study investigated whether Que postconditioning has any protective effects on myocardial ischemia/reperfusion (I/R) injury in vivo and its potential cardioprotective mechanisms. Male Sprague-Dawley rats were randomly allocated to 5 groups (20 animals/group): sham, I/R, Que postconditioning, Que+LY294002 [a phosphatidylinositol 3-kinase (PI3K)/Akt signaling pathway inhibitor], and LY294002+I/R. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Our previous data showed that overexpression of human TNNI3K promoted mouse embryonic stem cell differentiation into beating cardiomyocytes 20 . Moreover, overexpression of rat Tnni3k increased cardiac contractile function of ventricular myocytes in adult rats by enhancing phosphorylation of cardiac troponin I, indicating that TNNI3K enhanced cardiac function 21 . Additionally, Lai et al reported that intramyocardial administration of TNNI3K ‐overexpressed P19CL6 cells improved cardiac performance in mice with MI compared to the control group 23 .…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Our previous data showed that overexpression of human TNNI3K promoted mouse embryonic stem cell differentiation into beating cardiomyocytes 20 . Moreover, overexpression of rat Tnni3k increased cardiac contractile function of ventricular myocytes in adult rats by enhancing phosphorylation of cardiac troponin I, indicating that TNNI3K enhanced cardiac function 21 . Additionally, Lai et al reported that intramyocardial administration of TNNI3K ‐overexpressed P19CL6 cells improved cardiac performance in mice with MI compared to the control group 23 .…”
Section: Discussionmentioning
confidence: 97%
“…20 Moreover, overexpression of rat Tnni3k increased cardiac contractile function of ventricular myocytes in adult rats by enhancing phosphorylation of cardiac troponin I, indicating that TNNI3K enhanced cardiac function. 21 Additionally, Lai et al reported that intramyocardial administration of TNNI3Koverexpressed P19CL6 cells improved cardiac performance in mice with MI compared to the control group. 23 However, Tang et al found that transgenic DBA/2 J mice overexpressing human TNNI3K demonstrated a more rapid decline in fractional shortening in a left ventricular pressure overload model compared with non-transgenic controls, suggesting that TNNI3K accelerated cardiomyopathy progression after surgery.…”
Section: Tnni3k-cko Promotes Myocardial Apoptosismentioning
confidence: 99%
See 2 more Smart Citations
“…33 In vivo, TNNI3K protein is located at the cardiac sarcomeric Z-disc, 32 where it modulates contractile function. 32,33 Multiple QTL mapping studies for different cardiac traits have identified this locus, and ultimately, this gene, to be responsible for the observed phenotypic variation observed across inbred strains of mice. 16,18,[34][35][36] This convergence of seemingly distinct cardiac phenotypes on this single gene is likely attributable to 3 factors.…”
Section: Discussionmentioning
confidence: 99%